Efeito de diferentes enxaguatórios bucais sobre rugosidade de superfície de materiais utilizados para confecção de prótese tipo protocolo - Fraga, Marynara Moura [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The protocol type prosthesis is a treatment modality developed to rehabilitate total edentulous patients with osseointegrated implants and a total fixed prosthesis screwed to the implants. This modality of rehabilitation does not allow the patient to retire from the oral cavity for hygiene, being needed intraoral techniques for mechanical and chemical cleaning purposes, through mouthwashes. Some commercially available products may lead to adverse effects to the materials of confection of denture and to the patient himself. In this way, phytotherapy becomes an alternative to be researched. The objective of this study was to evaluate, in vitro, the effect of mouthwashes and a solution based on citronella oil (CN - Cymbopogon nardus) at 10,9%, in the alteration of the surface of materials used in the confection of prosthesis type protocol, being: two brands of artificial teeth (AT - Trilux e Vivodent), a thermally activated acrylic resin (TAAR) and a nickel-chromium (NiCr) alloy, being submitted to immersion and agitation for 180 minutes, simulating daily mouthwash for 6 months. 70 samples of TAAR and 70 metal samples were made and 140 teeth were used, being 70 upper central incisors of each commercial brand, distributed in 7 groups (n = 10) according to the rinse solution used: Control Group - (CG) without immersion; GI - artificial saliva; GII - Colgate PerioGard®; GIII - Colgate PerioGard® without ethanol; GIV - LISTERINE® ZERO; GV - LISTERINE® TARTAR CONTROL; GVI - Test solution formulated with 10.9% of the essential oil of citronella (CN). The surface change of the samples was evaluated in a rugosimeter (Ra). The data obtained in the surface roughness test were submitted to the analysis of fator variance and the averages of the repetitions of each group, to the Tukey's test (p <0.05). In the surface...

A prótese tipo protocolo é uma modalidade de tratamento desenvolvida para reabilitar pacientes desdentados totais com implantes osseointegrados e uma prótese total fixa aparafusada aos implantes. Esta modalidade de reabilitação não permite que o paciente a retire da cavidade oral para higienização, sendo necessárias técnicas intra-orais de limpeza mecânica e química, por meio de enxaguatórios bucais. Alguns produtos comercialmente disponíveis podem acarretar efeitos adversos aos materiais de confecção das próteses e ao próprio paciente. Desse modo, a fitoterapia passa a ser uma alternativa a ser pesquisada. O objetivo deste estudo foi avaliar in vitro, o efeito de enxaguatórios bucais comerciais e de uma solução teste à base do óleo de citronela (CN - Cymbopogon nardus) a 10,9%, na alteração de superfície de materiais utilizados na confecção de prótese tipo protocolo, sendo eles: duas marcas de dentes artificiais (DA - Trilux e Vivodent), uma resina acrílica ativada termicamente (RAAT) e uma liga de níquel-cromo (NiCr), sendo submetidas à imersão e agitação por 180 minutos, simulando bochechos diários por 6 meses. Foram confeccionadas 70 amostras de RAAT, 70 amostras de metal e utilizados 140 dentes, sendo 70 incisivos centrais superiores de cada marca comercial, distribuídos em 7 grupos (n=10), de acordo com a solução enxaguatória utilizada: Grupo Controle - (GC) sem imersão; GI - saliva artificial; GII - Colgate PerioGard®; GIII - Colgate PerioGard® sem etanol; GIV - LISTERINE® ZERO; GV - LISTERINE® TARTAR CONTROL; GVI - Solução teste formulada com 10,9% do óleo essencial de citronela (CN). A alteração de superfície das amostras foi avaliada em rugosímetro (Ra). Os dados obtidos no teste de rugosidade de superfície foram submetidos à análise de variância...
Keywords: Prótese total; Resinas acrílicas; Desinfecção; Cymbopogon; Teste de materiais; Denture, Complete